Effect of Prophylactic Intrathecal Pethidine on the Incidence of Shivering on Mothers Undergoing Cesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Girma, Timsel; Alemu, Wagaye; Assen, Sofia (Frontiers in Medicine, 2022)
Background Shivering is the most common and unpleasant complication of anesthesia with an incidence of 70.7% in cesarean section done under spinal anesthesia which is associated with cardiovascular and respiratory complications. Even though it causes such devastating complications; the prevention of shivering is not well investigated. This study aimed to assess the effect of intrathecal pethidine on the incidence and severity of shivering in patients undergoing cesarean section under Spinal anesthesia. Materials and Methods After obtaining ethical clearance double-blinded single centered a randomized controlled trial was conducted in a total of 86 pregnant mothers who were randomly allocated into two groups by computer-generated random number. Approximately 1 ml of 10 mg preservative-free pethidine was added to 12.5 mg of 0.5% bupivacaine for spinal anesthesia in the treatment group and 12.5 mg of 0.5% bupivacaine alone was given in the control group. Incidence and severity of shivering, as well as adverse effect was recorded intraoperatively, in post-anesthesia care unit (PACU) and ward. Independent sample t-test, Mann–Whitney U test and chi-square were used for analysis. A p-value less than 0.05 was considered statistically significant. Results Shivering was observed in 53.5 and 20.9% in the control and treatment groups, respectively, which was statistically significant with p = 0.002. The risk of developing shivering was reduced by 61% in the treatment group with (RR = 0.39 and CI of 0.205–0.745); the intensity of shivering was also higher in the control group than in the treatment group with p = 0.004. Considering an adverse effect, the incidence of PONV was not significantly different between with p > 0.05 while the incidence of pruritus was higher in the treatment group than the control group with p = 0.003. Conclusion Adding 10 mg of preservative free pethidine intrathecally during spinal anesthesia is effective in reducing incidence and severity of shivering, without causing significant adverse effects on mother.